Ajaran Moral dalam Serat Nitisastra - Djoko Pitoyo (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2004)
This article is an exploration of moral teachings of Serat Panitisastro, one of the most popular javanese literature in Majapahit era, and this Serat became popular again in Surakarta Kingdom in nineteenth century. The exploration is intended to reach better understanding of the moral teaching of the Serat as these are significantly rooted in the javanese culture.It will be demonstrated that the core of moral teaching in Serat Panatisastro is an ethics of virtues and the most important of which is a presentation of human virtues, to include the promotion of virtous conduct, and the prohibition of commiting insult. Each of the teaching emphasises self-image of the person and describes how she or he should plays a role in society based on this self-image.It is suggested that in the contemporary era, the moral teachings of Serat Panitisasto remain to have some relevance, while some need to be reinterpreted.